O direito ao trabalho da população transgênero - Sá, Ana Paula Suitsu de (2018)
This dissertation aims to show that our society excludes the transgender population from the formal job market, hindering the trans employee from the right to work. Starting from this point, we will show the main personality rights that are disrespected on the professional relationships involving transgender employees. Then, we will enlist some ways that could change said situation and promote the right to work to the transgender population, in conditions of dignity, with respect to all the kinds of gender identity. To achieve such goal, we'll use brazilian and foreign doctrine, as well as statistics researches and jurisprudence, to show the importance of the recognition - and celebration - of said differences, in order to allow to each and every one the right to work, regardless of one’s gender identity